Cuidados en el seguimiento postquirúrgico a un adulto de apendicitis. Santa Rosa 2022 - Campoverde Delgado, Linda Andrea; Ríos Socasi, Roxana Yaribel (Machala : Universidad Técnica de Machala, 2022)
INTRODUCTION: Appendicitis: it is the inflammation of the vermiform appendix, the most common cause of acute abdomen, it is a surgical disease, which occurs more frequently in emergency services. Patients with appendicitis present with: typical localized pain in the right lower quadrant. The WHO indicates that the highest incidence is during the 20 to 30 years of life, it is rare in children under five and over 50 years, the risk of presenting it is 16.33% in men and 16.34% in women. Annual incidence is 139.54 x 100,000 inhabitants; is associated with overweight and obesity, 50 years ago 15 out of 100,000 people died from acute appendicitis, currently the probability of dying from appendicitis is less than 0.1%. OBJECTIVE: To analyze the post-surgical follow-up of an adult with appendicitis, Santa Rosa 2022, through a case study to carry out a Nursing intervention proposal. METHOD: Type of qualitative research through a case study, the research is focused on the clinical method that appropriates the scientific method in a logical and mandatory order, its methodology based on the patient.
INTRODUCCION: Apendicitis: es la inflamación del apéndice vermiforme, la causa más común de abdomen agudo, es una enfermedad quirúrgica, que se presenta con mayor frecuencia en los servicios de urgencias. Los pacientes con apendicitis presentan: dolor típico localizado en el cuadrante inferior derecho. La OMS, indica que la mayor incidencia es durante los 20 a 30 años de vida, es rara en menores de cinco y mayores de 50 años, el riesgo de presentarla es de 16.33% en hombres y 16.34% en mujeres. Incidencia anual es de 139.54 x 100,000 habitantes; se asocia con sobrepeso y obesidad, hace 50 años 15 de cada 100,000 personas morían por apendicitis aguda, actualmente la probabilidad de morir por apendicitis es inferior al 0.1%. OBJETIVO: Analizar el seguimiento posquirúrgico a un adulto de apendicitis, santa rosa 2022, mediante el estudio de caso para realizar una propuesta de intervención de Enfermería. METODO: Tipo de investigación cualitativo a través de un estudio de caso, la investigación está enfocado en el método clínico que se apropia del método científico en un orden lógico y de obligado cumplimiento, de su metodología puesta en función del paciente
Keywords: APENDICITIS AGUDA; SEGUIMIENTO DOMICILIARIO POSTOPERATORIO